2007
DOI: 10.1175/2007jcli1533.1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the West African Monsoon Jump

Abstract: The observed abrupt latitudinal shift of maximum precipitation from the Guinean coast into the Sahel region in June, known as the West African monsoon jump, is studied using a regional climate model. Moisture, momentum, and energy budget analyses are used to better understand the physical processes that lead to the jump. Because of the distribution of albedo and surface moisture, a sensible heating maximum is in place over the Sahel region throughout the spring. In early May, this sensible heating drives a sha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
112
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(125 citation statements)
references
References 27 publications
13
112
0
Order By: Relevance
“…ENSO, on the other hand, only has a weak (negative) correlation with precipitation. These results make sense from a precipitation sources point of view : the Sahel receives part of its rainfall from the Mediterranean but the coastal region much less (see Figure S8b) [also, e.g., Druyan and Koster, 1989 ;Nieto et al, 2006;Hagos and Cook, 2007;Schicker et al, 2010;Keys et al, 2011], although it has been speculated that part of the crossdesert transport of Mediterranean moisture into the Sahel could be an artifact of the moisture tracking models [Dirmeyer, 2011]. Nonetheless, these results are confirmed by previous observational and modeling studies that found similar relationships between SST and West African precipitation [e.g., Vizy and Cook, 2002 ;Rowell, 2003].…”
Section: Van Der Ent and Savenije: Precipitation And Correlation Withmentioning
confidence: 93%
See 1 more Smart Citation
“…ENSO, on the other hand, only has a weak (negative) correlation with precipitation. These results make sense from a precipitation sources point of view : the Sahel receives part of its rainfall from the Mediterranean but the coastal region much less (see Figure S8b) [also, e.g., Druyan and Koster, 1989 ;Nieto et al, 2006;Hagos and Cook, 2007;Schicker et al, 2010;Keys et al, 2011], although it has been speculated that part of the crossdesert transport of Mediterranean moisture into the Sahel could be an artifact of the moisture tracking models [Dirmeyer, 2011]. Nonetheless, these results are confirmed by previous observational and modeling studies that found similar relationships between SST and West African precipitation [e.g., Vizy and Cook, 2002 ;Rowell, 2003].…”
Section: Van Der Ent and Savenije: Precipitation And Correlation Withmentioning
confidence: 93%
“…The contribution of region 13 (South China Sea) peaks a bit later in August-November, when the contribution of region 12 is weakening and the monsoon period is in the declining phase. Likewise, region 9 (Gulf of Guinea) is clearly the source area of the West African monsoon during June-September [see also, e.g., Druyan and Koster, 1989;Hagos and Cook, 2007], although there is also a strong local moisture recycling component in West Africa during the rainy season [Savenije, 1995b[Savenije, , 1995aNieto et al, 2006;van der Ent and Savenije, 2011;Keys et al, 2012].…”
Section: Seasonal Variationsmentioning
confidence: 99%
“…Each simulation uses a 90-s time step and 90 km horizontal resolution. Previous work indicates that this resolution is sufficient for producing a sufficiently accurate representation of the summer climate of the Sahel (e.g., Hsieh and Cook 2005, 2008Hagos and Cook 2007) and for capturing land/atmosphere feedbacks (Patricola and Cook 2008). The horizontal resolution is finer than that of typical GCMs and provides information to aid impacts analysis on the regional scale.…”
Section: Methodology For Generating Confident Future Climate Predictionsmentioning
confidence: 99%
“…Ramel et al (2006) using the MAR regional climate model have attributed the monsoon onset to an abrupt shift in the SHL position resulting from differences in surface albedo between the Sahel and Sahara desert. Hagos and Cook (2007), also using a regional climate model (RCM), found that the surface sensible heat drives a shallow meridional circulation and moisture convergence at the latitude of the sensible heating maximum, which leads to an inertial instability responsible for the abrupt meridional shift of rainfall maxima. Sijikumar et al (2006) using the Mesoscale Model MM5 found a deepening of the SHL followed by an enhanced westerly moisture advection from the eastern Atlantic ocean during the WAM onset.…”
Section: Introductionmentioning
confidence: 99%